Heterogeneity and permeability estimation of pore-throat structure at different scales in deep tight sandstone reservoirs: A case study of Paleogene Hetaoyuan Formation in Anpeng area, Nanxiang Basin, China. - Yan Zhu; Yunfei Yang; Yuheng Zhang; Lin Liu; Hengquan Li; Qin Sang (PLoS ONE)
Clarifying the pore-throat size and pore size distribution of tight sandstone reservoirs, quantitatively characterizing the heterogeneity of pore-throat structures, is crucial for evaluating reservoir effectiveness and predicting productivity. Through a series of rock physics experiments including gas measurement of porosity and permeability, casting thin sections, scanning electron microscopy, and high-pressure mercury injection, the quality of reservoir properties and microscopic pore-throat structure characteristics were systematically studied. Combined with fractal geometry theory, the effects of different pore throat types, geometric shapes and scale sizes on the fractal characteristics and heterogeneity of sandstone pore throat structure are clarified. On this basis, the estimation model of tight sandstone permeability was established. The results indicate that the reservoir physical properties in the study area are poor, the pore types are mainly dissolved pores, and the pore size is mainly distributed in the nano to submicron range. The fractal dimension fitting curve obtained based on the non-wetting phase model has obvious turning points, indicating that the pore-throat structure has multi-scale characteristics. The turning point of fractal dimension divides the pore-throat structure of tight sandstone into large-scale pore-throats with good connectivity (reticular or beaded pore-throats) and small-scale pore-throats with poor connectivity (dendritic or capillary pore-throats), indicating that tight sandstone has binary pore structure characteristics. The geometry of large-scale pore-throat is complex, which is difficult to meet the self-similar characteristics, with the average fractal dimension is 3.72. The small-scale pore-throat morphology is close to the capillary and has obvious fractal characteristics, with the average fractal dimension is 2.22. There are many small pores and micropores in the reservoir, and the pore volume has a significant positive correlation with the total porosity of the rock, but the contribution to the permeability is low. The development degree of large-scale pore throat is an important factor affecting the physical properties of tight sandstone. The turning point radius of fractal curve and the comprehensive fractal dimension can be used as good indicators for permeability estimation.